Prenatal stress and risk of behavioral morbidity from age 2 to 14 years: The influence of the number, type, and timing of stressful life events - Robinson, M.; Mattes, E.; Oddy, W.; Pennell, C.; van Eekelen, A.; McLean, N.; Jacoby, P.; Li, Jianghong; de Klerk, N.; Zubrick, S.; Stanley, F.; Newnham, J. (Cambridge University Press, 2011)
The maternal experience of stressful events during pregnancy has been associated with a number of adverse consequences for behavioral development in offspring, but the measurement and interpretation of prenatal stress varies among reported studies. The Raine Study recruited 2900 pregnancies and recorded life stress events experienced by 18 and 34 weeks’ gestation along with numerous sociodemographic data. The mother’s exposure to life stress events was further documented when the children were followed-up in conjunction with behavioral assessments at ages 2, 5, 8, 10, and 14 years using the Child Behavior Checklist. The maternal experience of multiple stressful events during pregnancy was associated with subsequent behavioral problems for offspring. Independent (e.g., death of a relative, job loss) and dependent stress events (e.g., financial problems, marital problems) were both significantly associated with a greater incidence of mental health morbidity between age 2 and 14 years. Exposure to stressful events in the first 18 weeks of pregnancy showed similar associations with subsequent total and externalizing morbidity to events reported at 34 weeks of gestation. These results were independent of postnatal stress exposure. Improved support for women with chronic stress exposure during pregnancy may improve the mental health of their offspring in later life.